Cura animarum as hope care: Towards a theology of the resurrection within the human quest for meaning and hope - Louw, D. J. (HTS teologiese studies, 2014)
The following critical questions are posed: is hope the antidote of dread and despair or a kind of escapism from the harsh realities of anguish and suffering? What is meant by hope in Christian spirituality and how is hope connected to a theology of the resurrection? Is resurrection hope merely a kind of cheap triumphantalism and variant of a theologia gloriae? The basic assumption is that the notion of the resurrection can contribute to ‘the thickening of alternative stories of faith’. A theologia resurrectionis is about the reframing of life by means of a radical paradox: ‘Where, O death is your victory? Where, O death is your sting?’ If pastoral caregiving is indeed about change and hope, the resurrection describes an ontology of hope by which human beings are transformed into a total new being. Beyond the discriminating and stigmatising categories of many social and cultural discourses on our being human, resurrection theology defines hope as a new state of mind and being. The identity of human beings is therefore not determined by descent, gender, race or social status, but by eschatology (new creation.) Hope care is primarily about a new courage to be. It opens up different frameworks for meaningful living within the realm of human suffering.